FUNCTIONAL APPLICATION OF THE INTERNAL CONTROL SYSTEM IN AUTONOMOUS INSTITUTIONS - Chaykovskaya L.A.,; Turishcheva T.B.,; Akhmadeev R.G., (Scientific Journal of Pedagogy and Economics, 2020)
Modern business conditions are based on the laws and characteristics of the development of market relations. Successful and stable activity of any business entity today directly depends on the effectiveness of the management system, the most important element of which is properly organized control. In the activities of any business entity, the place, role and importance of control are as important as accounting, management and analysis. The domestic science of control has rather deep roots, and the multifaceted nature and depth of the concept of “control” are closely related to the concepts of “management” and “management accounting”. In conditions of increasing competition, when the problems of increasing the effectiveness of control are significantly updated, the issues of organizing internal control, its development and integration are becoming more relevant. The study of the category of "internal control", its subjects and objects, the place in the management process allows us to identify in its structure individual species characterized by a targeted orientation and methodological features. The practical implementation of the internal control system should be carried out in accordance with the basic principles of its effective organization, which are closely interconnected, and the procedure for combining them to a greater extent depends on the prevailing specific business conditions and circumstances. Integration of the internal control system into the general management system will ensure the reliability of information at various levels, as well as significantly reduce the potential for making erroneous management decisions. The principles of making a choice when implementing a rational and economically reasonable accounting policy of an autonomous institution depend directly on the valid regulations of the accounting standards of the public sector system of the economy. This aspect makes it possible to influence not only the effectiveness of the use of material, labor and financial resources, but also to ensure a proper level of capital units’ turnover, to obtain additional internal sources of capital investments financing and current assets, to attract external resources to expand the scope of an autonomous institution. The application of various models of internal control, including elements of a risk-oriented approach allows to carry out to the right degree conceptual process of organizing enterprise control. The model of the internal control system of an autonomous institution suggested by the authors takes into account a systematic approach, risk orientation considering factors of the internal and external environment, incorporating the model in business processes, with regard to the ultimate goal of implementation - increasing the efficiency of business processes while reducing expenses and increasing profit in the financial responsibility centers. Indicative management model is widely used as the foundation of management. As a rule, it is based on a spatial vision of internal control, and as an analysis, depending on the activity type of an economic entity, the business processing is allocated, taking into account the influence of various indicators that reflect the factors influence of the external and internal environment, in particular, in the context of parameters of competitive advantage. We consider the use of an effective model to be the most promising model of internal control. Based on the author's idea of an integrated model of internal control, its main components will be: a systematic approach, a focus on risks, taking into account factors of the internal and external environment, incorporating the model in business processes and financial responsibility centers. Furthermore the main object of the suggested model of internal control will be risks arising as a result of the influence of factors of the internal and external environment. The purpose of the suggested model is to increase the efficiency of business processes existing in the economic entity while simultaneously reducing expenses and increasing profits in financial responsibility centers. Considering that the element “control environment” of internal control within the framework of the current legislation has changed to the institutional internal environment, it is noteworthy that the introduction into application practice of institutional environment of an autonomous institution internal control consists of the following levels: external and internal. The external environment in the form of formal and informal institutes is prevailing, having an impact on the internal environment of an economic entity, represented by its own specific cultural and functional “micro institutes” (formal and informal).